Scientific Notation of Technology Park Structure on the Basis of Stakeholders' Environment Models - Maltseva, Anna (International Journal of Economics and Financial Issues, 2015)
The paper is focused on the development of scientific and theoretical concepts of technology park structures (TPS) as main subjects of modern innovative regional economy. The author suggests using the concept of environmental in conjunction with the stakeholders' theory, which allows to create possibilities for determination of the position and significance of a variety participants of TPS for management purposes. This ensures the balance of priorities in the activities of TPS to meet the needs of different stakeholders. Based on the methodology the main stakeholders groups and their objectives in relation to the TPS are identified; the importance of the Mitchell's model is allocated; the structure of resource relations between the stakeholders of TPS in accordance with the Rowley's network model is shown. The author proposes a strategic model of stakeholders' management, which allows developing a unified approach to manage stakeholder groups, as well as a matrix model with the application of certain aspects of the Savage's model. Using obtained results in practical activities of TPS enables to create significant benefits for the expansion of the stakeholders network and their involvement in joint activities and special management system based on the principle of ‘soft power'. Keywords: technology park structure, science and technology park, stakeholders, internal environment, innovative environment, innovative company, anchor resident JEL Classifications: O3; O14; R1